Roundtable: "Muscle builder" supplements - Eichner, R. E.; King, D.; Myhal, M.; Prentice, B.; Ziegenfuss, T. N. (Sports Science Exchange, 1999)
The expert panel agreed to discuss the use and misuse of several "muscle builder" supplements and to provide their views on the extent to which coaches, personal trainers, physicians and others in leadership positions should recommend dietary supplements to athletes. Key points: Protein powders, protein-carbohydrate "weight gainers," creatine, and various "andro" products are popular among athletes and others who hope to gain muscle mass by using these supplements. Scientific evidence is sparse that any of these "muscle builder" supplements produces noticeable muscle growth beyond that achieved with a sound program of resistance training and overall good nutrition. However, many athletes fail to follow even the most basic principles of good training and nutrition. Athletes, especially the young, should be taught to expect gradual improvements in performance from many years of hard training and good nutrition; supplements will not give a "quick fix" to performance problems.